Consensus guidelines for pressurized intraperitoneal aerosol chemotherapy: Technical aspects and treatment protocols. Issue 4 (April 2022) - Hübner, Martin; Alyami, Mohammad; Villeneuve, Laurent; Cortés-Guiral, Delia; Nowacki, Maciej; So, Jimmy; Sgarbura, Olivia; ,; Abba, Julio; Afifi, Adnane; Mortensen, Michael Bau; Bhatt, Aditi; et al.
Abstract: Background: Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is increasingly used to treat patients with peritoneal cancer. A recent survey demonstrated considerable diversification of current practice of PIPAC raising issues of concern also regarding safety and efficacy. The study aim was to reach consensus on best practice of PIPAC treatment. Methods: Current practice was critically discussed during an expert meeting and the available evidence was scrutinized to elaborate a 33-item closed-ended questionnaire. All active PIPAC centers were then invited to participate in an online two-round Delphi process with 3 reminders at least. Consensus was defined a priori as >70% agreement for a minimal response rate of 70%. Results: Forty-nine out of 57 invited PIPAC centers participated in Delphi 1 and 2 (86%). Overall, there was agreement for 21/33 items. Consensus was reached for important aspects like advanced OR ventilation system (91.8%), remote monitoring (95.9%), use of the PRGS (85.7%) and use of a safety checklist (98%). The drug regimens oxaliplatin (87.8%) and cisplatin/doxorubicin (81.6%) were both confirmed by the expert panel. Important controversies included number and location of Biopsies during repeated PIPAC and the combination of PIPAC with additional surgical procedures. Conclusion: This consensus statement aims to allow for safe and efficacious PIPAC treatment and to facilitate multi-center analyses of the results. Additional preclinical and clinical studies are needed to resolve the remaining controversies.